1999
DOI: 10.7326/0003-4819-131-10-199911160-00004
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Neoplasms in Long-Term Survivors of Bone Marrow Transplantation

Abstract: The spectrum of neoplasms and immunosuppressive treatment with cyclosporine for chronic graft-versus-host disease as dominant risk factors indicate that immunosuppression is the major cause of malignant neoplasms in patients receiving marrow transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 244 publications
(116 citation statements)
references
References 24 publications
4
106
2
4
Order By: Relevance
“…As for conditioning regimen, radiation-containing regimen was not significantly associated with LM after HSCT in our series, although radiation was reported to be associated with LM after HSCT. [3][4][5] This is probably because of absolute low patient number who developed LM. Recently, Flu-based preconditioning regimen is widely used in HSCT for SAA from MSD or alternative donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for conditioning regimen, radiation-containing regimen was not significantly associated with LM after HSCT in our series, although radiation was reported to be associated with LM after HSCT. [3][4][5] This is probably because of absolute low patient number who developed LM. Recently, Flu-based preconditioning regimen is widely used in HSCT for SAA from MSD or alternative donors.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative incidence of LM was 0.8% at 10 years and 2.5% at 20 years, respectively, which was much lower than those in previous reports. [3][4][5][6] As for conditioning regimen for SAA in patients with LM, four received radiation-containing regimen and one non-irradiation regimen. Comparisons of cumulative incidence of LM between radiation and non-radiation regimen did not reach statistical significance (2.5 vs 3.1% at 20 years, P ¼ 0.718).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from EBMT of 1036 recipients surviving >5 years (median follow-up=10.7 years, range 5–22) did not find donor-recipient histocompatibility to be a significant risk factor for development of new malignancies. 129 Unpublished data from the Fred Hutchinson Cancer Research Center (FHCRC) found that the relative risk of SN in allogeneic HCT recipients, after adjustment for both aGVHD and cGVHD, was higher in those recipients who received peripheral blood stem cell (PBSC) grafts compared to bone marrow (RR=1.6, 95%CI=1.2–2.10, p=0.001). The fewer number of UCB transplants and their shorter follow-up precluded an accurate assessment of risk in UCB recipients.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
“…180 Other virus-related cancers are rare, but observed elevations in risk for cervical cancer (HPV) and liver cancer (HCV, hepatitis B virus [HBV]) support the likely importance of oncogenic viruses in cancer risk after allogeneic HCT. 24,39,43,181 A single case reports suggests the possibility of donor T-cells acquiring human T-lymphotropic virus (HTLV1). 182 Polyomaviruses also represent an emerging group of viruses requiring study because of their potential to cause epithelial malignancy.…”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%